Bilateral botryoid nephroblastoma: a rare cause of renal failure. (7th September 2012) - Conlon, Niamh; Teoh, Chia Wei; Pears, Jane; O'Sullivan, Maureen
Abstract : The authors describe the case of a 16-month-old girl who presented with bilateral hydronephrosis and renal failure secondary to bilateral renal pelvic botryoid Wilms' tumour (nephroblastoma). The term 'botryoid' describes an intrapelvic polypoid renal Wilms tumour, either extending from the renal parenchyma or primarily pelvis-based tumour. Both tumours filled the renal pelvis and extended down the proximal ureter, with no intraparenchymal tumour seen. Bilateral intralobar nephrogenic rests were present. Histological examination demonstrated triphasic nephroblastoma, with focal rhabdomyomatous differentiation of the stromal element bilaterally. Postchemotherapy, the patient underwent bilateral nephrectomy. Post complete resection of her bilateral disease, this patient has had an excellent outcome. This is only the third reported case of bilateral botryoid Wilms' tumour. While the condition is extremely rare, it should be included in the differential diagnosis of a young child with bilateral renal pelvic masses.